Development of basic technologies for improvement of breeding and cultivation of Japanese gentian - Nishihara, Masahiro (Breeding science, 2018)
Japanese gentians are the most important ornamental flowers in Iwate Prefecture and their breeding and cultivation have been actively conducted for half a century. With its cool climate and large hilly and mountainous area, more than 60% of gentian production in Japan occurs in Iwate Prefecture. Recent advances in gentian breeding and cultivation have facilitated the efficient breeding of new cultivars; disease control and improved cultivation conditions have led to the stable production of Japanese gentians. Molecular biology techniques have been developed and applied in gentian breeding, including the diagnosis of viral diseases and analysis of physiological disorders to improve gentian production. This review summarizes such recent approaches that will assist in the development of new cultivars and support cultivation. More recently, new plant breeding techniques, including several new biotechnological methods such as genome editing and viral vectors, have also been developed in gentian. We, therefore, present examples of their application to gentians and discuss their advantages in future studies of gentians